A doctor in the Great War - Davidson, Andrew 1969- (Marble Arch Press, 2014)
"As a twenty-five-year-old medical officer and one of the first doctors to win the Military Cross, Fred Davidson took countless photographs while he served in the trenches from 1914-1915. Though he took them illegally, more than 250 of the photographs shot by Davidson and his fellow officers survived and are now shared for the first time in this harrowing, eye-catching, and poignant narrative of the Great War. In A Doctor in the Great War, author Andrew Davidson-the grandson of Fred-depicts the everyday lives of soldiers, both on and off duty: from the parade ground at Glasgow's Maryhill to the brothels of Armentieres, from the band of brothers who dubbed themselves "Old Contemptibles" to the original folding Kodak and Ansco cameras they used. It is the story of the 1st Cameronians, who achieved notoriety for selling the Great War's earliest front line photographs. And it is a deeply personal account of the pictures that have been passed down for three generations, describing the men who fought with Fred Davidson, the conditions they served in, the battles they saw, and the horrors they endured."...Provided by publisher